Implementation of Government Regulation Number 53 of 2010 concerning Dicipline of Civil Servants: Case of Higher Education Institution in Semarang - Prasetyowati, Sri Redjeki; Wedhatami, Bayangsari; Sinta, Radini (Faculty of Law Universitas Negeri Semarang, 2022)
Cases of violations of ASN discipline are like an iceberg phenomenon, the number of cases that appear on the surface/reported doesn't seem that many, but of course there are still many uninformed cases, this is a concern in itself. Even though the rules contained in Government Regulation Number 53 of 2010 have been implemented concerning PNS/ASN Discipline, cases of disciplinary violations still occur. One of the reasons for the stipulation of PP No. 53 of 2010 concerning Discipline for Civil Servants as a substitute for PP no. 30 of 1980 concerning the discipline of Civil Servants due to the demands of society for improving the performance and service of civil servants in line with the implementation of bureaucratic reforms. In addition to PP No. 53 of 2010, the State Civil Service Agency (BKN) has also prepared a replacement for PP no. 10 of 1979 concerning the evaluation of the implementation of the work of civil servants, which so far is known as DP3, namely PP No. 46 of 2014.